Back to the rationale of a Multidimensional Vulnerability Index (MVI) and its components to enhance its consistency - Patrick Guillaumont (Fondation pour les études et recherches sur le développement international (FERDI), 2022)
The MVI project was born from a UN General Assembly Resolution that gives it legitimacy, conditioned by its economic rationale (see the previous notes prepared for UNDESA-OHRLLS for their support to the work of the High-Level Panel on MVI: Guillaumont, Feindounou, Wagner, 2022; and Guillaumont, 2022).
Keywords: 330